2017
DOI: 10.1016/j.neurobiolaging.2017.02.014
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of APOE e4 and poor glycemic control predicts white matter hyperintensity growth from 73 to 76

Abstract: We examined whether apolipoprotein E (APOE) status interacts with vascular risk factors (VRFs) to predict the progression of white matter hyperintensities (WMHs) on brain MRI scans over a specific period of life in older age when the risk of dementia increases. At age 73 years, baseline VRFs were assessed via self-reported history of diabetes, hypertension, smoking, and hypercholesterolemia, and via objective measures of blood HbA1c, body mass index, diastolic and systolic blood pressure, and blood high-densit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 42 publications
3
13
0
Order By: Relevance
“…The homozygous ε4 genotype was revealed to be a significant predictor of WMH load. The finding is consistent with evidence of increased WMH volume in ε4 carriers in the UK Biobank cohort and longitudinal evidence of WMH progression associated with the ε4 genotype (Cox et al, 2017). Here we also replicate the finding from Lyall et al (2019), in which there is no age interaction observed with APOE ε4 status in terms of total WMH load, contrary to some reports that APOE ε4 effects are most prominent in older age (Schiepers et al, 2012).…”
Section: The Spatial Distribution Of Individual Cerebrovascular Risk supporting
confidence: 91%
“…The homozygous ε4 genotype was revealed to be a significant predictor of WMH load. The finding is consistent with evidence of increased WMH volume in ε4 carriers in the UK Biobank cohort and longitudinal evidence of WMH progression associated with the ε4 genotype (Cox et al, 2017). Here we also replicate the finding from Lyall et al (2019), in which there is no age interaction observed with APOE ε4 status in terms of total WMH load, contrary to some reports that APOE ε4 effects are most prominent in older age (Schiepers et al, 2012).…”
Section: The Spatial Distribution Of Individual Cerebrovascular Risk supporting
confidence: 91%
“…There are also likely to be many other lifestyle factors that are important for brain health that are not measured here (and serological markers which may offer greater precision than diagnosis information) which may well interact with differences in genetic susceptibility to such factors (e.g. 49,50 , and should undoubtedly be a priority for future study in large brain imaging samples. This is especially important given that the majority of brain structural variation remains unexplained by the specific factors examined in this report.…”
Section: Limitationsmentioning
confidence: 99%
“…The pathogenesis of WMH is most likely driven by ischemia resulting from hypertensive small vessel disease, but amyloid angiopathy may also be another underlying cause of extensive WMH ( Tomimoto, 2015 ). More recently, carriage of the apolipoprotein E4 genotype was reported to affect the relationship between glucose alterations and WMH ( Livny et al, 2016 ; Cox et al, 2017 ). Thus, patients with AD have a variety of pathologies, including small vessel disease, and may be more susceptible to the effects of glucose exacerbation on WMH progression.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, an association between fluctuations in HbA1c levels and WMH was reported in diabetes patients who carry the apolipoprotein E4 allele ( Livny et al, 2016 ), which is a strong genetic risk factor for AD. Additionally, apolipoprotein E4 carriers who are elderly and have diabetes or higher HbA1c levels exhibited greater WMH progression than other individuals ( Cox et al, 2017 ). These findings suggest that patients with diabetes who have experienced AD-related pathological changes in the brain may be more susceptible to metabolic stress than other patients.…”
Section: Introductionmentioning
confidence: 99%